Coulomb crystal mass spectrometry in a digital ion trap - Deb, N; Pollum, L; Smith, A; Keller, M; Rennick, C; Heazlewood, B; Softley, T (2015)
We present a mass spectrometric technique for identifying the masses and relative abundances of Coulomb-crystallized ions held in a linear Paul trap. A digital radiofrequency waveform is employed to generate the trapping potential, as this can be cleanly switched off, and static dipolar fields subsequently applied to the trap electrodes for ion ejection. Excellent detection efficiency is demonstrated for Ca+ and CaF+ ions from bi-component Ca+/CaF+ Coulomb crystals prepared by reaction of Ca+ with CH3F. A quantitative linear relationship is observed between ion number and the corresponding integrated TOF peak, independent of the ionic species. The technique is applicable to a diverse range of multi-component Coulomb crystals - demonstrated here for Ca+/NH3+/NH4+ and Ca+/CaOH+/CaOD+ crystals - and will facilitate the measurement of ion-molecule reaction rates and branching ratios in complicated reaction systems.